2008
DOI: 10.1073/pnas.0801394105
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 inhibits neutrophil efferocytosis

Abstract: Phagocytosis of apoptotic cells, also called efferocytosis, is an essential feature of immune responses and critical for the resolution of inflammation. Plasma and tissue levels of plasminogen activator inhibitor-1 (PAI-1), an inhibitor of fibrinolysis, are elevated in inflammatory conditions, including sepsis and acute lung injury, in which activated neutrophils accumulate in tissues and contribute to organ dysfunction. In this study, we explored the potential involvement of PAI-1 in modulating neutrophil eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 30 publications
6
106
0
Order By: Relevance
“…Notably, the urokinase plasminogen activator receptor has recently been described as a novel engulfment receptor (20), although its prophagocytic role remains controversial (21). Moreover, Das and Plow (22) have described the histone 2B-dependent recruitment of plasminogen to PS-rich surfaces, and it has been shown that PAI impairs apoptotic cell removal (23). These studies taken together with our work suggest that dysregulation of the plasminogen system might lead to deranged apoptotic cell clearance.…”
Section: Discussionsupporting
confidence: 51%
“…Notably, the urokinase plasminogen activator receptor has recently been described as a novel engulfment receptor (20), although its prophagocytic role remains controversial (21). Moreover, Das and Plow (22) have described the histone 2B-dependent recruitment of plasminogen to PS-rich surfaces, and it has been shown that PAI impairs apoptotic cell removal (23). These studies taken together with our work suggest that dysregulation of the plasminogen system might lead to deranged apoptotic cell clearance.…”
Section: Discussionsupporting
confidence: 51%
“…Although increased levels of PAI-1 and inhibition of plasmin generation are found in the lungs and circulation of critically ill patients with sepsis or ALI (28,40), recent studies have also shown that PAI-1 can affect a broad range of cellular functions independent of its effects on coagulation, including cell adhesion, proliferation, migration, and viability (6,21,36). In particular, PAI-1 can facilitate neutrophil chemotaxis, enhance release of cytokines by Toll-like receptor 4-stimulated neutrophils, and diminish the uptake of apoptotic neutrophils by macrophages (23,26).…”
mentioning
confidence: 99%
“…Of note, diminished neutrophil apoptosis is a well characterized finding during acute lung injury in experimental models and in patients with this condition (39,41,42). Furthermore, in addition to its antiapoptotic effects, vitronectin may also exacerbate the severity of acute lung injury through decreasing the uptake and clearance of apoptotic neutrophils by alveolar and tissue-based macrophages (12), thereby allowing the apoptotic neutrophils to progress to necrotic death with associated release of proinflammatory contents into the pulmonary parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The vitronectin SMB domain has been shown to bind plasminogen activator inhibitor (PAI) -1, uPAR, collagen, and thrombin-antithrombin complexes. Previous studies demonstrated that vitronectin and its binding partners, PAI-1 and the uPA, can diminish the phagocytosis of apoptotic cells by macrophages, a process referred to as efferocytosis (11)(12)(13). However, a role for vitronectin in modulating neutrophil apoptosis has not been described.…”
mentioning
confidence: 95%